Creativity and Innovation of Assistance for Victims of Domestic Violence: Between Law and Practices - Baindowi, Salimi Muhammad (Journal of Creativity Student, 2019)
Violence against women in households in quantitative terms has increased significantly and is accompanied by an increase in intensity and quality. Domestic violence results in physical, psychological, sexual, and neglectful suffering or suffering, including the threat of unlawful deeds, coercion, or deprivation of liberty within the scope of the household. Victims of domestic violence require assistance from the sender to the concerned investigator with a copy to the vertical institution, Komnas HAM and Komnas Perlindungan Anak.